QUESTION OF IMPROVING THE INSTITUTION OF REPRESENTATION IN CASES ON RECOGNITION OF A CITIZEN AS HAVING LIMITED LEGAL CAPACITY OR LEGALLY INCAPABLE - Subkhonov Sherali Muhammad Ugli (American Journals Publishing, 2024)
This article analyzes civil procedural legislation regarding the institution of representation in cases on recognition of a citizen as having limited legal capacity or legally incapable. The reasoning of experts in this field is presented, as well as the author’s own opinion on the issue of the participation of a representative in cases on recognition of a citizen as having limited legal capacity or legally incapable. A comparative legal analysis of the institution of representation in civil proceedings with foreign countries is also carried out. The author pays special attention to the gaps in the legislation and puts forward his own proposals for eliminating them.
Keywords: Representative, civil process, attorney, official representative, incapacity, special proceedings.